Variation of Phenology of Flacourtia rukam in Two Different Habitats and Their Relation to Rainfall, Dry Days, and the Plant Water Status - Darmayanti, Agung Sri; Ariffin; Waluyo, Budi; Ariesoesilaningsih, Endang (Jurnal Manajemen Hutan Tropika, 2024)
Phenological shifts in the emergence of vegetative and generative parts, occur due to the response of plants to water received due to climate change. The rukam tree (Flacourtia rukam (Zoll & Moritzi)) is a local Indonesian plant with potential as an edible fruit and antioxidant agent, but its existence is increasingly rare. F. rukam can be found in Pasuruan, East Java, including Purwodadi Botanical Garden (PBG) as collected plants and Sekarmojo Village as cultivated plants. These populations show a shift in phenology, but this has never been studied. This study aimed to analyze the spatial variation of the phenology of two rukam populations and its relation to plant water status, rainfall quantity (RQ), and drought days (DD). This research was conducted on two individual trees at each location, was conducted from August 2020 to October 2022 using secondary data from BMKG, such as daily rainfall and the number of days without rain. Phenology was directly observed every week with an estimated abundance of numbers 1-4; plant water status was observed by calculating relative water content (RWC); soil physical analysis was carried out in mid-season. Data were analyzed by Mann-Whitney test and SEM WarpPLS. The results showed differences in phenology in the phases of leaf fall, flower buds, young fruit, and ripe fruit on the trees in the different locations. The decreased RQ in the past month significantly reduced the RWC value of F. rukam in both places, while the number of DD contributed to a decrease in the RWC value in PBG only, not in Sekarmojo. In both sites, decreasing the RWC of the rukam increased the abundance of fallen leaves and the chances of flowering. Rainfall and drought days affected plant phenology directly or indirectly through RWC mediation. In both places, RQ had a direct positive and significant effect on blooming flowers and new leaves but had negative effect on fallen leaves. While DD had a positive effect on leaf fall, flower formation, and fruit ripening, but had a negative effect on the appearance of young fruit (in PBG). Indirectly, RQ mainly affected several phenological parameters, while DD did not affect all phenological parameters.